Imunocastração e ractopamina na qualidade de lombos suínos processados com sal e tripolifosfato - Silva Iocca, Andreia Fernanda; Lucas, Daniel Silva; Fausto, Daiane Aparecida; Delgado, Eduardo Francisquine; Nedel Pertile, Simone Fernanda; Janzantti, Natlia Soares [UNESP] (Empresa Brasil Pesq Agropec, 2015)
The objective of this work was to evaluate the effect of immunocastration and supplementation with ractopamine in the quality of pork loin enhanced with salt and sodium tripolyphosphate. Treatments consisted of the sexual condition of the swine (females, physically castrated and immunocastrated males) and supplementation or not with ractopamine in finishing diet. The loins subjected to the enhancement with sodium tripolyphosphate and salt were evaluated as to physical-chemical, microbiological, and sensory parameters. There was no interaction between sexual condition and ractopamine on fresh pork loin characteristics. The addition of ractopamine in the diet increased the shear force in fresh loins. There was also no effect of sexual condition nor of ractopamine in purge loss and loin protein content. Loins of immunocastrated animals had less weight loss by cooking, whereas loins of animals non-supplemented with ractopamine showed higher moisture than those supplemented. Enhancement decreases the shear force of the cuts, which was lower in the immunocastrated animals without ractopamine supplementation. Immunocastration provided pork loins with high a* and L* values. Differences in the appearance and texture of pork loins, regardless of sexual condition and ractopamine, are not perceived by consumers, showing that enhancement standardizes the cuts.

O objetivo deste trabalho foi avaliar o efeito da imunocastração e da suplementação com ractopamina na qualidade do lombo suíno processado com sal e tripolifosfato de sódio. Os tratamentos consistiram de condição sexual dos suínos (fêmeas, machos castrados fisicamente e imunocastrados) e suplementação ou não com ractopamina na dieta de terminação. Os cortes de lombos submetidos ao processamento com tripolifosfato de sódio e sal foram avaliados quanto aos parâmetros físico-químicos, microbiológicos e sensoriais. Não houve interação entre condição sexual e ractopamina nas características do lombo cru. A adição de ractopamina na dieta aumentou a força de cisalhamento dos lombos crus. Também não houve efeito da condição sexual nem da ractopamina na perda de peso por exsudação e no teor proteico dos lombos. Lombos de animais imunocastrados apresentaram menor perda de peso por cocção, enquanto lombos de animais não suplementados com ractopamina apresentaram maior umidade do que os dos suplementados. O processamento diminuiu a força de cisalhamento dos cortes, que foi menor nos animais imunocastrados sem suplementação com ractopamina. A imunocastração proporcionou lombos com altos valores de a* e L*. Diferenças na aparência e na textura dos lombos suínos, independentemente da condição sexual e da ractopamina, não são percebidas pelos consumidores, o que mostra que o processamento padroniza os cortes.
Immunocastration and ractopamine in the quality of pork loin enhanced with salt and tripolyphosphate
Keywords: Beta-adrenergic agonist; Animal welfare; Gonadotropin; Injection marinade; Meat quality; Sodium tripolyphosphate; Agonista β-adrenérgico; Bem-estar animal; Gonadotropina; Marinação por injeção; Qualidade de carne; Tripolifosfato de sódio